Efek Jenis dan Komposisi Lamina Kayu terhadap Sifat Balok Laminasi Silang dari Kayu Hutan Rakyat - Greitta Kusuma Dewi; Tibertius Agus Prayitno; Ragil Widyorini (Faculty of Forestry Universitas Gadjah Mada, 2024)
Community forests offer diverse wood species and quantities, potentially meeting the increasing demand for wood-building materials driven by the green building concept. The diverse species have varied specific gravity. Combining wood species and cross-lamination engineering could improve the strength and dimensional stability of low-density and medium-density wood from community forests. Therefore, this research aimed to determine the effect of wood species and laminae composition on the properties of 5-ply cross-laminated beams (CLB). The 5-ply CLB was made in 5 cm x 5 cm x 112 cm with 1 cm laminae thickness. The species used were sengon, jabon, and mahogany, with acacia as enforcement. This research also compared homogeneous and heterogeneous laminae composition. The results showed that wood species and laminae composition significantly affect the mechanical properties. Heterogeneous compositions had higher mechanical properties than homogeneous compositions. The delamination test revealed that the CLB had high water resistance on cold and hot immersion even though the beams used up to three wood species.